Association between parents’ concerns about eating and sleeping problems and social-emotional development in Chinese children aged 3 to 6 years - Hu, Tongxi; Liu, Shaoying; Zhan, Jianying; Xu, Luxin; Zhou, Yanqing (Frontiers in Public Health, 2023)
Background: Parents' parenting beliefs have a major influence on their children's eating and sleeping problems and emotional socialization. However, the relationship between parent's concerns about eating or sleeping problems and social-emotional development is unclear.We used a convenience sampling method to investigate 997 parents of preschool children aged 3 to 6 in Hangzhou, China, and asked them to complete the "Ages & Stages Questionnaire: Social-Emotional (2nd Edition)" (ASQ: SE-2) and the Survey of Concerns about Children's Eating and Sleeping Problems. To examine the relationship between children's social-emotional development and their parents' concerns about their eating or sleeping problems, binary logistic regression was used.Results: There were 218 children (21.9%) with a suspected social-emotional development delay, and 273 parents (27.4%) were concerned about their children's eating or sleeping problems, which mainly focused on ill-balanced eating, bad eating habits, and difficulty falling asleep. The rate of suspected social-emotional development delay in children with the co-occurrence of eating and sleeping problems (37.8%) was significantly higher than those with only eating problems (29.7%), only sleeping problems (24.4%), and those with no eating or sleeping problems (18.8%) (p < 0.05). A binary logistic regression analysis showed that parents' concerns about the co-occurrence of eating and sleeping problems (OR = 2.52, p = 0.01) and only eating problems (OR = 1.71, p = 0.004) were risk factors for children's social-emotional development. In addition, boys were more likely than girls to have suspected social-emotional development delay (OR = 1.49, p = 0.01).Children whose parents were concerned about only eating or the co-occurrence of eating and sleeping problems were linked to have a higher risk of suspected social-emotional development delay.